Предмет: Алгебра,
автор: polina9513
решите уравнение (х+3а)*(х-2а)-(х+а)*(х-3а)=0;
Ответы
Автор ответа:
0
Перемножаем
Сокращаем
2-х+а=0
Умножаем не -1
Получается
х-а=2
(Наверное)
Сокращаем
2-х+а=0
Умножаем не -1
Получается
х-а=2
(Наверное)
Автор ответа:
0
Неверно же, что у тебя получилось после перемножения?
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: Математика,
автор: manegood25
Предмет: Математика,
автор: serejamolchanov66
Предмет: Геометрия,
автор: walleqq
Предмет: Математика,
автор: nebesa